Dampak Sengketa Kepulauan Senkaku antara Jepang - Cina Terhadap Stabilitas Keamanan Jepang - Tjhang Zahra Anisa Pramaiseilla (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
The Senkaku Islands are rich in oil and gas resources, which has led Japan and Cina to claim each other that the Senkaku Islands belong to them. The impact of the dispute on Japan's security stability makes the senkaku islands and Japanese territories threatened and insecure because Cina conducts military operations by arming fishermen to become